Estudio de impacto ambiental de la explotación de materiales petreos en la mina san pablo, en la parroquia Valencia, cantón Valencia, provincia de los Ríos, periodo 2015 - Vallejo Tulcán, James Armando (2015)
Mining of stone materials in the San Pablo River mine has been developing legally and technically in mining, environmental, social and economic issues, but still triggers social affectations, landscape, physical and biotic and negative impacts to the soil, air and water. Considering technical methods to manage and improve the stone material exploitation help, but just prolongs the landscape deterioration, air quality, life quality, road networks, among others: that ultimately lead to socio-environmental problems between population and activity, which is why this research suggests consider certain technical and environmental stages for proper processing of stone material from the exploration, development, project planning, production and finally the closing stage and suggested abandonment rejection….